Археологічні дослідження ділянок біля Десятинної церкви 2008 р. - Івакін, Г.Ю.; Козюба, В.К.; Комар, О.В.; Манігда, О.В. (Археологічні дослідження в Україні, 2009)
The paper presents a short description of the results of the research in 2008 at the area near Desyatynna Church. Several stages of functioning and rebuilding of the fosse of Old Kyiv hill-fort, which by the finds from the filling of the fortifications could be dated to the end of the 9 th — the 10 th c., were determined. Near the southern wall of the temple 2 pagan burials of the 10 th c. were discovered, one of which contained 43 glass and cornelian beads.